Development and Application of Creative Problem Solving in Mathematics and Science: A Literature Review - Widya, Widya; Nurpatri, Yeni; Indrawati, Ena Suma; Ikhwan, Khairul (Universitas Islam Negeri Raden Intan Lampung, 2020)
The purpose of this study is to review the development and application of creative problem solving learning model especially in the last 1 decades. Research method used in this study was literature review. We collected more than 20 references related to the history, development, and application of the CPS model. Data collection technique used was through literature study. The results of this study obtained some types of CPS models such as CPS version Treffinger, CPS version Osborn, and CPS published by Creative Education Foundation. The CPS model proposed by the Creative Education Foundation is the latest and best model because it was developed to improve the previous CPS model. Each CPS Model has different steps with some similar goals. CPS is applied at several levels of education for learning Natural Sciences and Mathematics. CPS has a significant influence on the achievement of cognitive competence and problem solving skills